„Ludy Morza” na tle przeobrażeń kulturowych w strefie pontyjsko-bałkańskiej w 2. poł. II tys. p.n.e. - Cieszewska, Justyna (Folia Praehistorica Posnaniensia, 2018)
The project intended to investigate cultural, social and political situation of the second half of the second millenium BC in the catchment area of the Black and the Aegean Seas. The cultural transformations taking place at that time in the Pontic-Balkan area have been discussed within this framework. In terms of chronology, it covers the period between 1500 and 1150 BC, that is prior to the expansion of the Sea Peoples and shortly afterwards. A particular attention has been drawn on events taking place around the 12th century BC. The primary aim of this work was to specify a nature of interrelations, socio-political structure as well as cultural correlations between Eastern and Southern Europe. These issues were discussed in a broad spatial perspective, partially in reference to temperate Europe, northern Pontic zone, Eastern, Central and Western Balkans and Aegean- Anatolian zone. This allowed for a comprehensive overview of the “political-historical” situation. The core of the discussion was concentrated on the genesis of the so-called Sea Peoples, whose invasion of the late 13th and 12th centuries BC affected broad areas of the eastern Mediterranean. The study has been based upon the assumption on a possibility of producing a comprehensive overview of archaeological and historical materials making possible to interrogate the Sea Peoples both from the northern (Central and Eastern Europe and the Balkans) and southern perspective (eastern Mediterranean). The most important part of the study has been devoted to detailed analysis of archaeological artefacts and historical documents (written and iconographic sources) making possible to address these issues. Evidence of Sea Peoples invasion from Central and Eastern Europe comprise swords of the Naue II type, swords and daggers of the Krasny Mayak type, spearheads and arrows, a decorative motive of waterfowl heads, hatchets and the so-called barbarian ceramic, among others.